ANALISIS KINERJA PRODUKSI DAN STRATEGI PENGEMBANGAN AGROINDUSTRI KOPI BUBUK 49 DI KOTA BANDAR LAMPUNG - Intifaza, Ajeng Tazkia; Haryono, Dwi; Rahmalia, Dian (Lampung University, 2025)
This research aims to analyze the production performance and development strategy of Ground Coffee 49 Agroindustry. The research used a case study method in Ground Coffee 49 Agroindustry in Bandar Lampung City. Respondents in this study were the owner and employee of the Ground Coffee 49 Agroindustry, representatives of the Dinas Koperasi dan UKM Kota Bandar Lampung, representatives of the Disperindag Provinsi Lampung, expert lecturers from Lampung University, and partners of the Ground Coffee 49 Agroindustry. The data collection period in this study was conducted from September to November 2023. The analytical tools used in this research are production performance analysis, evaluation of internal and external factors, IE matrix, SWOT matrix, and QSPM matrix. The results showed that the production performance of Ground Coffee 49 Agroindustry based on 6 types of measurements namely productivity, capacity, quality, delivery speed, and process speed was good, while based on aspect of flexibility was still not good. The main strength of Ground Coffee 49 Agroindustry is attractive product packaging. The main weakness of the agroindustry is the limited number of workers. The main opportunity for agroindustry is cooperation with related agencies. The main threat of agroindustry is the number of more innovative competing products. The prioritized development strategy for Ground Coffee 49 Agroindustry is the use of targeted advertised features on social media to reach the right target consumers, increasing production technology in business development, and consistent product promotion by utilizing social media. Key words: Agroindustry, Ground Coffee, Performance, Strategy Development